On orthogonally additive functions with big graphs - Baron, Karol (Annales Mathematicae Silesianae, 2018)
Let E be a separable real inner product space of dimension at least 2 and V be a metrizable and separable linear topological space. We show that the set of all orthogonally additive functions mapping E into V and having big graphs is dense in the space of all orthogonally additive functions from E into V with the Tychonoff topology.